THE INFLUENCE OF THE DOW JONES INDEX ON THE COMBINED STOCK PRICE INDEX (IHSG) - I Dewa Putu Reza Amanta Suputra; Anak Agung Bagus Putu Widanta (Adisam Publisher, 2024)
Global development is basically considered an opportunity and a challenge at the same time. Indonesia, which is a developing country, is a country with a small economy (Small Open Economy). A country with a small economy is a country whose national economy is not yet developed, meaning that the country's role and influence in the global economy is not large enough. The stock market has historically been an indicator that is sensitive to business cycles and is also the most influential variable in the government's leading indicator index. The aim of this research is to prove that Indonesia is a small open economy whose business cycles are influenced by developed countries (Big Economy). This research was conducted on the Indonesian Stock Exchange using secondary data in the form of time series obtained through trusted websites. The time series data used is monthly data starting from 2019 - 2022 (4 years). The amount of data observed in this study was 48 data. The analysis technique used in this research is multiple linear regression. The research results show that the Fed Interest Rate, World Oil Prices and the Dow Jones Index simultaneously have a positive effect on the IHSG. The research results also show that the three independent variables, namely the Fed Interest Rate, World Oil Prices and the Dow Jones Index have a partial positive effect on the IHSG.